2018
DOI: 10.1080/10641963.2018.1465074
|View full text |Cite
|
Sign up to set email alerts
|

Current prescription status of antihypertensive drugs in Japanese patients with hypertension: Analysis by type of comorbidities

Abstract: In 2014, the Japanese Society of Hypertension (JSH) issued revised guidelines for hypertension management. To assess adherence to the guidelines, this retrospective study evaluated the real-world status of antihypertensive drug prescribing for Japanese patients with hypertension, classified by comorbidity: diabetes mellitus, dyslipidemia, gout/hyperuricemia and renal diseases. Data on 59,867 hypertensive patients who received their first prescription for antihypertensive therapy between April 2014 and March 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(40 citation statements)
references
References 23 publications
3
32
1
2
Order By: Relevance
“…The present analyses show that the real‐world use of FDC varies depending on the desired combination and number of agents prescribed. Overall, the majority of patients in the present study were prescribed one or two antihypertensive agents, and the most frequently prescribed classes of agents were CCB and ARB, consistent with similar analyses carried out in Japan using pharmacy prescription data . We found that the prescription rate of CCB + ARB FDC was relatively low overall, and did not increase depending on the total number of antihypertensive agents prescribed.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…The present analyses show that the real‐world use of FDC varies depending on the desired combination and number of agents prescribed. Overall, the majority of patients in the present study were prescribed one or two antihypertensive agents, and the most frequently prescribed classes of agents were CCB and ARB, consistent with similar analyses carried out in Japan using pharmacy prescription data . We found that the prescription rate of CCB + ARB FDC was relatively low overall, and did not increase depending on the total number of antihypertensive agents prescribed.…”
Section: Discussioncontrasting
confidence: 99%
“…The most common comorbidities were dyslipidemia (56.8%) and heart diseases (52.0%; Table ). Overall, 58.6% of patients were prescribed two or more antihypertensive agents, and the most frequently prescribed classes of agent were CCB and ARB with rates of approximately 35% …”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations